On the Search for the Synchrotron Cosmic Web - Hodgson, Torrance James Tate (Curtin University, 2022)
On the very largest of scales, the Universe is predicted to emit a faint radio signature as a result of ongoing structure formation: the so-called synchrotron cosmic web. This radio signature promises to shed light on vast, cluster-scale magnetic fields. In this work, we use both simulations to better understand the nature and distribution of this radio signal, and make several attempts towards practical detection using low frequency radio interferometers.